INFLUENCE OF ENTREPRENEURIAL INNOVATION AND GOVERNMENT POLICY INCENTIVES ON SMALL BUSINESS PERFORMANCE IN BORDER COMMUNITIES OF ADAMAWA STATE AND CAMEROON - MUSA, IBRAHIM; SAGAGI , MURTALA SABO; ALIYU , MUKHTAR SHEHU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This study sought to examine how entrepreneurial innovations and government policy incentives influences small business performance in border communities of Nigeria and Cameroon. Emphasis is placed on Adamawa State border with Cameroon. Past studies have demonstrated that Mubi, Sahuda, Kwaja and Belel borders of Adamawa State with northern Cameroon are prominent gate ways for the flow of livestock, cowpea, sesame, grains and manufactured goods to all parts of Nigeria, Cameroon and Chad. However, businesses operating along the corridors remained largely small and have been experiencing certain challenges including border closure, infrastructure, entrepreneurial innovations and limited government policy incentives, among others. It is therefore imperative to examine factors that conditioned the businesses in border communities to remain informal and small. A Survey design was used for the study. The study used stratified probability sampling method to draw 428 samples from 1840 owner/managers of small businesses in border communities of Adamawa State and Cameroon. The result of PLS-SEM shows that limited government policy Incentives (with P- Values of 0.000) and entrepreneurial Innovation (with P- Values of 0.020) have significant Positive relationship with border small business Performance in border communities of Adamawa State and Cameroon. The study recommends government policy intervention to support small businesses through provision of infrastructures (such as roads and electric power supply) and capacity building training on small business among small business operators by regional agencies of the Nigeria and Cameroon (such as SMEDAN and world bank).